Business Model Canvas: Online Business Strategy at Pekanbaru Fishing Equipment Store - Muhammad Fahrozi; Nia Anggraini; Irsyadi Zain; Erfa Okta Lussianda; Awliya Afwa (International Journal of Sustainable Applied Sciences, 2024)
This research explores the feasibility of an online business strategy for "Toko Serba Pancing" (Fishing Equipment Store) in Pekanbaru, Indonesia, considering the shift in consumer behavior from traditional to online platforms, triggered by the COVID-19 pandemic. The study employs qualitative analysis using Porter's 5 Forces, Business Model Canvas, and SWOT analysis. The findings reveal that "Toko Serba Pancing" adopts a Business-to-Customer (B2C) model in its online strategy, focusing on providing unique fishing bait not readily available elsewhere. SWOT analysis indicates potential opportunities outweighing threats externally, with strengths outweighing weaknesses internally. Despite identified weaknesses, the store has significant potential for development. The business strategy that can be implemented is Webrooming via social media, search engines, and e-commerce.